Development of A Project Based Learning Hybrid Mode Module to Train Science Skills for Phase D Students - Maiyanti, Aziza Anggi; Imtiyaza, Muhammad Iffat; Laili, Ummiy Fauziyah; Panse, Vishal R (Program Studi Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2024)
One of the subjects in the 8th grade merdeka curriculum is natural science (IPA). Science is involved in education in a variety of ways, from the simple to the complex, from the unclear or abstract to concrete solutions to problems. In an effort to teach students science skills in Phase D science subjects, this research aims to develop a hybrid project-based PJBL (PJBL) module. The method used in this research is Research and Development (R&D) with quantitative descriptive data analysis techniques which consist of several stages, namely needs analysis, module design, expert validation, field trials, and product revision. This research was carried out at MTsN 3 Kediri, with class VIII students. The conclusion of this research is that the project based learning hybrid mode module is very suitable to be used to improve students' science skills based on student response questionnaires and validation by experts that have been carried out.